Analysis of pregnenolone and dehydroepiandrosterone in rodent brain: cholesterol autoxidation is the key - William Griffiths (The Journal of Lipid Research, 2009)
Pregnenolone (PREG) and dehydroepiandrosterone (DHEA), and their respective sulfated forms PREGS and DHEAS, were among the first steroids to be identified in rodent brain. However, unreliable steroid isolation and solvolysis procedures resulted in errors, particularly in the case of brain steroid sulfates analyzed by radioimmunology or GC-MS of liberated free steroids. By using a solid-phase extraction recycling/elution procedure, allowing the strict separation of sulfated, free, and fatty acid esters of PREG and DHEA, PREGS and DHEAS, unlike free PREG, were not detected in rat and mouse brain and plasma. Conversely, considerable amounts of PREG and DHEA were released from unknown precursor(s) present in the lipoidal fraction, distinct from fatty acid ester conjugates. Chromatographic and mass spectrometric studies of the nature of the precursor(s) showed that autoxidation of brain cholesterol (CHOL) was responsible for the release of PREG and DHEA from the lipoidal fraction. When inappropriate protocols were used, CHOL was also the precursor of PREG and DHEA obtained from the fraction assumed to contain sulfated steroids. In contrast, free PREG was definitely confirmed as an endogenous steroid in rat brain. Our study shows that an early removal of CHOL from brain extracts coupled to well-validated extraction and fractionation procedures are prerequisites for reliable measurements of free and conjugated PREG and DHEA by GC-MS or other indirect methods.